Pengaruh Media Sosial dan Gaya Hidup Terhadap Perilaku Konsumtif Generasi Z Pada Pembelian Sneakers: (Studi Kasus Pada Mahasiswa Universitas Bandar Lampung) - Try Oustin; Habiburahman Habiburahman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to determine the effect of social media and lifestyle on the consumptive behavior of the Z generation in purchasing sneakers. This type of research uses qualitative research by distributing questionnaires to students at Bandar lampung university with total of 52 respondents.the results of this study indicate the social media influences consumptive behavior. Generation Z in purchasing sneakers while lifestyle variables have no effect on the consumptive behavior of generation Z in purchasing sneakers.